Bibliometric analysis of the global research development of bone metastases in prostate cancer: A 22-year study - Chen, Yongming; Tang, Chen; Shen, Zefeng; Peng, Shengmeng; Wu, Wanhua; Lei, Zhen; Zhou, Jie; Li, Lingfeng; Lai, Yiming; Huang, Hai; Guo, Zhenghui (Frontiers in Oncology, 2022)
Background Prostate cancer (PCa) is the second most diagnosed cancer in men. Most PCa-related deaths result from metastatic disease. Metastases occur most often in the bones (90%). However, the current treatments for bone metastases in PCa are not very effective. Here we present an overview of the current research situation of bone metastases in PCa, focusing on hotspots and trends. Methods We searched the Web of Science Core Collection database for publications related to bone metastases in PCa published between 1999 and 2021. We used VOSviewer, CiteSpace, and a bibliometric online platform to perform a bibliometric analysis of countries, institutions, authors, journals, references, and keywords. Results A total of 4,832 related articles were included in the present study. The USA published the most articles in the field, followed by China and England. The University of Texas MD Anderson Cancer Center is the leading institution in the research field of bone metastases in PCa. Saad F, from Canada, has made great achievements in this area by publishing 91 related articles. Prostate is the journal which published most related articles, and Mundy GR, 2002, Nat Rev Cancer is the most cited article in this field. Furthermore, the analysis of author keywords can be divided into five clusters: (1) the diagnosis of PCa, (2) the mechanism of bone metastasis, (3) drug treatments of bone metastases, (4) radiotherapy of bone metastases, and (5) the treatments and the prognosis of PCa. Conclusions Together, mCRPC has been the hottest topic in the PCa in recent years. CT is the most common diagnostic method for bone metastases. Enzalutamide and radium-223, as the important treatments for bone metastases of PCa, bring about widespread attention. Furthermore, the researchers focus on the tumor microenvironment and biomarkers to explore the mechanism and the therapeutic targets of bone metastases of PCa.